Accumulation of Long-Lived Photogenerated Holes at Indium Single-Atom Catalysts via Two Coordinate Nitrogen Vacancy Defect Engineering for Enhanced Photocatalytic Oxidation - Zhang, Jingjing (Advanced materials (Deerfield Beach, Fla.), 2024)
© 2024 The Author(s). Advanced Materials published by Wiley‐VCH GmbH.